1859 Ky. Acts 245 - (:unkn) unknown (My University, 1859)
An Act to Amend an Act Entitled "An Act to Reduce to One of the Several Acts in Relation to the Town of Harrodsburg,"§ 23: Prohibited "any slave or free person of color, any gun, pistol, bowie knife, slung shot, sword cane, or other weapon used for the purpose of offence or defence."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES